1993
DOI: 10.1063/1.109324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electric and magnetic fields on THz radiation

Abstract: We report measurement of the influence of electric and magnetic fields on optically induced THz electromagnetic radiation from semiconductors at normal incidence. The measurements show that electric and magnetic fields strongly influence the amplitude and phase of transient carrier-generated THz radiation, but do not affect THz optical rectification generated by the bulk second order nonlinear susceptibility, for static electric fields up to 104 V/cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The radiated THz field is proportional to the optical pump power and is due to a combination of OR, 176,242 bulk DFG 243 and photocarrier acceleration in the surface field of the semiconductor. 244,245 T-ray emission from semiconductor surfaces is influenced by the magnetic field surrounding the emitter, 246,247 which can be used to switch or enhance the generation efficiency. 248~252 T-ray emission from an unbiased GaAs wafer in a switchable magnetic field is shown in Fig.…”
Section: Pulsed Photomixingmentioning
confidence: 99%
“…The radiated THz field is proportional to the optical pump power and is due to a combination of OR, 176,242 bulk DFG 243 and photocarrier acceleration in the surface field of the semiconductor. 244,245 T-ray emission from semiconductor surfaces is influenced by the magnetic field surrounding the emitter, 246,247 which can be used to switch or enhance the generation efficiency. 248~252 T-ray emission from an unbiased GaAs wafer in a switchable magnetic field is shown in Fig.…”
Section: Pulsed Photomixingmentioning
confidence: 99%
“…However this limitation can be overcome by using a magnetic field to change the direction of the transient current. 5 Recently, Sarakura et al 6 have reported a substantial enhancement of the efficiency of THz generation at bare InAs surfaces by a moderate magnetic field. They claimed average emitted THz powers of ϳ0.7 mW using a 1 W average power Ti-sapphire pump laser.…”
Section: Introductionmentioning
confidence: 99%
“…When illuminated at 0° angle of incidence, little or no THz emission is therefore observed in the back-reflected direction, as mentioned earlier. The application of the magnetic-field creates a Lorentz force acting on the moving charges, which adds a vertical in-plane component to the current, and thus creates a vertically polarized THz electric-field component [15][16][17][18]. We note that historically, before the exact cause for the magnetic field-induced changes in THz emission for semiconductors was known, an enhancement factor was used to phenomenologically describe the magnetic-field induced changes in the emitted THz amplitude.…”
Section: Basal-plane Surface Illuminationmentioning
confidence: 99%